MANAJEMEN PEMERINTAHAN DINAS KESEHATAN DALAM PENANGGULANGAN STUNTING DI DESA KEPAYANG KABUPATEN ROKAN HULU TAHUN 2018 - Sherly Deffi Octaviani; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Stunting is a condition in which a person's height is shorter than the height of other people in general (who are the same age). Stunting occurs in infants (0-11) months and children under five (12-59) months due to chronic malnutrition, especially in 1,000 first day of life (HPK). The Regional Government of Rokan Hulu Regency is trying to reduce the stunting rate in Rokan Hulu. The Rokan Hulu District Health Office is the agency responsible for regulating health services in the Rokan Hulu Regency area. The prevention of stunting reduction aims to carry out efforts to reduce stunting in Riau Province, especially in Rokan Hulu Regency.                        This study seeks to answer the researcher's questions as follows: How is the Management of the Health Office in dealing with stunting in Rokan Hulu Regency in 2018, what factors are the obstacles in overcoming stunting in Kepayang Village, Rokan Hulu Regency in 2018. This research also aims to describe Management of the Health Office in overcoming stunting in Kepayang Village, Rokan Hulu Regency, then also to describe the factors that are obstacles in overcoming stunting in Rokan Hulu Regency. This type of research used by the author in this study is descriptive. Data collection techniques are interviews, literature study and documentation. The data analysis technique in this study was carried out qualitatively.The results of the study explain that the Government Management in tackling stunting in Kepayang Village, Rokan Hulu Regency has not been maximized due to the lack of coordination of Regional Apparatus Organizations (OPD) in the problem of stunting prevention, so that several indicators consist of planning policies and programs, organizing government structures, financial management, coaching. and personnel development, general decision-making, program management, political oversight. Not going well. In its implementation there are also several inhibiting factors such as Human Resources, Budget, and Infrastructure / Facilities and Infrastructure.Keywords: government management, prevention, stunting.